The Relationship Of Ear Picking Habits With The Incident Of Otitis Externa At Roemani Muhammadiyah Hospital Semarang - Martono, Wahyu Budi; Nina Anggraeni Noviasari; Reynaldy Aditya Putra; Wahyu Puspita Eka Almira (Ahmad Dahlan Medical Journal, 2024)
Acute ear canal inflammation, or otitis externa, is brought on by bacterial, fungal, or viral infections. One of factor that cause inflammation of the outer ear is a change in the pH in the ear canal, which is usually normal or acidic. When the pH becomes alkaline, protection against infection decreases. Edema of the squamous epithelium can result from the picking habit's reduction of the protective layer. It can cause local trauma which causes bacteria to enter through the skin, inflate and cause exudate. The aim of this study was to determine the relationship between ear picking habits and the incidence of otitis externa at Roemani Muhammadiyah Hospital. This study uses a cross-sectional design and observational analysis. Using a purposive sampling technique, samples of all ENT polyclinic patients who met the inclusion and exclusion criteria between January 2019 and December 2020 at Roemani Muhammadiyah Hospital in Semarang City, Central Java Province totaled roughly 36 individuals. The responders were asked to fill out a questionnaire. It has several questions that were utilized as study guidelines to gather research data and as note-taking tools. According to the findings, ear plucking and otitis externa were significantly correlated with a prevalence value of 0.000 <0.05. There is a significant relationship between the habit of picking the ears and otitis externa in ENT polyclinic patients, Roemani Muhammadiyah Hospital, Semarang.